2021
DOI: 10.3389/fbioe.2021.760724
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Methylation Modification 5-Methylcytosine Impacts Immunity Characteristics, Prognosis and Progression of Oral Squamous Cell Carcinoma by Bioinformatics Analysis

Abstract: Disorders pertaining to 5-methylcytosine (m5C) modifications are involved in the pathological process of many diseases. However, the effect of m5C on the tumorigenesis and progression of oral squamous cell carcinoma (OSCC) remains unclear. In this study, we integrated the genomic and clinical data of 558 OSCC samples to comprehensively evaluate m5C modification patterns. Based on 16 m5C methylation regulators, two m5C modification clusters were identified with distinct tumor immune microenvironment (TIME) char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Furthermore, m5C methylation can also participate in the regulation of the TME. Gao et al [ 44 ] revealed that patients with oral squamous cell carcinoma with high m5C methylation scores had lower immune activity and a poor prognosis. What roles do m5C-related lncRNAs play in the TME?…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, m5C methylation can also participate in the regulation of the TME. Gao et al [ 44 ] revealed that patients with oral squamous cell carcinoma with high m5C methylation scores had lower immune activity and a poor prognosis. What roles do m5C-related lncRNAs play in the TME?…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that there was no significant correlation between the m 5 C score and TMB, indicating that the m 5 C score is independent of TMB. It has been reported in previous studies low m 5 C score was related to a better prognosis of oral squamous cell carcinoma and papillary thyroid carcinoma patients ( 19 , 70 ). In our study, high m 5 C score indicated better immunotherapy response and prognosis.…”
Section: Discussionmentioning
confidence: 67%
“…For example, in CD4 + T cells from patients with SLE, the levels of the m 5 C writer NSUN2 and methylated m 5 C genes were found to be decreased ( 13 ). In cutaneous melanoma, lung adenocarcinoma, lung squamous cell carcinoma, and other cancer types, bioinformatic analysis have shown that m 5 C regulators modulate the tumor immune microenvironment, act as immunotherapy indicators and were related to patients’ prognosis ( 14 19 , 22 , 60 64 ). These studies firmly proved that m 5 C regulators were differentially expressed and modulated the immunotherapy response in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gao et al ( Gao et al, 2019 ) found that high expression of NSUN2 could promote the proliferation and tumorigenesis of gallbladder carcinoma cells both in vitro and in vivo by closely cooperating with ribosomal protein L6. Recently, the role of m5C modification in cancers, including lung cancer, colon carcinoma, bladder cancer, and thyroid carcinoma, has been explored ( Pan et al, 2021a ; Pan et al, 2021b ; Chen et al, 2021 ; Gao et al, 2021 ; Geng et al, 2021 ; Gu et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ; Xu et al, 2021 ). In addition, He et al ( He et al, 2020a ) built a gene signature including 2 m5C regulators and found that it could effectively predict the prognosis of HCC.…”
Section: Introductionmentioning
confidence: 99%